The Secret of Time: Reconfiguring Wisdom in the Dead Sea Scrolls - Bakker, Arjen F. (Brill, 2023)
This book contributes to the rethinking of the Dead Sea Scrolls as an essential and integral part of Judaism in the Greco-Roman period. The Qumran manuscripts attest to the reconfiguration of Jewish wisdom concepts in this period. Strikingly, reflection on time as the organizing principle behind all of reality is formative for these emerging concepts, which are expressed by the enigmatic phrase rāz nihyeh. The secret of time invites us to venture beyond existing categorizations and explore a rich conceptual framework that is manifested across a wide range of texts, beyond generic categories, and overcoming the sectarian divide.